China Inside Out - Pál Nyíri, Joana Breidenbach (Central European University Press, 2005)
The ""war on terror"" has generated a scramble for expertise on Islamic or Asian ""culture"" and revived support for area studies, but it has done so at the cost of reviving the kinds of dangerous generalizations that area studies have rightly been accused of. This book provides a much-needed perspective on area studies, a perspective that is attentive to both manifestations of ""traditional culture"" and the new global relationships in which they are being played out. The authors shake off the sha...